Role of business process models in requirements engineering - Ashraf, Fatima; Abdullah, Mohd Syazwan (2009)
The goal of requirements engineering is to create a complete, consistent requirements specification of a desired system in order to establish the requirements at an abstract level.Business process modeling in the early phases of requirement engineering is rather useful.This paper examines business process modeling for the development of information systems.It presents the role of Business Process Model in Requirements Engineering.The process of Requirements Engineering is highlighted in this paper.It explains thoroughly the groundwork, requirements elicitation and business process model. Several Business Process Models are discussed at later part and how they are related to Requirements Engineering.It is enlightened the importance of Business Process Models in Requirements Engineering to get more precise and accurate requirements.